Analysis of Service Quality and Trust on Customer Satisfaction of Ojek Online in Banyuwangi - Titin Lestariningsih (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2021)
Gojek online is a partner for two-wheeled drivers who can contribute 8.2 trillion per year to the Indonesian economy. This study is to analyzes the factors that influence online motorcycle taxi customer satisfaction in Banyuwangi. This research is a type of explanatory quantitative research with causal prediction measuring the strength of the relationship between variables. The population in this study is application users (consumers) who have received online motorcycle taxi services in 2021 in Banyuwangi. The sample is 100 respondents. The data were processed using SPSS 21 and SmartPLS 3.0. The hypothesis was processed using Structural Equation Modeling Path Least Square (SEM-PLS). The results of this study indicate that service quality has a significant positive effect on customer satisfaction and trust. Trust has no significant effect on customer satisfaction. Service quality has no significant effect on customer satisfaction with trust moderation. This research is to improve the service quality of online motorcycle taxi partners.